Новітні роботи Прикарпатської експедиції - Романець, В.Ф.; Мацкевий, Л.Г.; Кочкін, І.Т. (Археологічні дослідження в Україні, 2009)
The main works related to the preparation of the monuments to the 30 th anniversary of excavations on the territory of Starunya. Protective research resulted in discovering the sites Bukivna XV (Palaeolithic), Bukivna XVI (Mesolithic), Luka XVIII (Trypillya BI), and Bukivna XVII (a barrow).